A Global Inventory of Ice-Related Morphological Features on Dwarf Planet Ceres: Implications for the evolution and current state of the cryosphere - Sizemore, Hanna; Schmidt, Britney E.; Buczkowski, D.L.; Sori, Michael M.; Castillo-Rogez, J.; Berman, D. C.; Ahrens, C.; Chilton, H.; Hughson, K.; Duarte, K.; Otto, Katharina A.; Bland, M.; et al. (Journal of Geophysical Research: Planets, 2018)
We present a comprehensive global catalog of the geomorphological features with clear orpotential relevance to subsurface ice identified during the Dawn spacecraft’s primary and first extended missions at Ceres. We define eight broad feature classes and describe analyses supporting their genetic links to subsurface ice. These classes include relaxed craters; central pit craters; large domes; small mounds; lobate landslides and ejecta; pitted materials; depressions and scarps; and fractures, grooves, and channels. Features in all classes are widely distributed on the dwarf planet, consistent with multiple lines of observational evidence that ice is a key component of Ceres’ crust. Independent analyses of multiple feature types suggest rheological and compositional layering may be common in the upper ~10 km of the crust. Clustering of features indicates that ice concentration is heterogeneous on nearly all length scales, from ~1 km to hundreds of kilometers. Impacts are likely the key driver of heterogeneity, causing progressive devolatilization of the low latitude and midlatitude crust on billion-year timescales but also producing localized enhancements in near surface ice content via excavation of deep ice-rich material and possible facilitation of cryomagmatic and cryovolcanic activity. Impacts and landslides may be the dominant mechanism for ice loss on modern Ceres. Our analysis suggests specific locations where future high-resolution imaging can be used to probe (1) current volatile loss rates and (2) the history of putative cryomagmatic and cryovolcanic features. The Cerean cryosphere and its unique morphology promise to be a rich subject of ongoing research for years to come.